The electrocardiographic early repolarization pattern in athletes: Normal variant or sudden death risk factor? - Tanguturi, V. K.; Noseworthy, P. A.; Newton-Cheh, C.; Baggish, A. L. (Sports Medicine, 2012)
The clinical evaluation of athletes during symptom evaluation or pre-participation screening often involves interpretation of the 12-lead electrocardiogram (ECG). Differentiating abnormal ECG findings suggestive of underlying cardiovascular disease from benign findings caused by exercise-induced cardiac adaptations can be challenging, and recent clinical guidelines have been created for this purpose. One of the most common ECG findings in athletes is the early repolarization pattern (ERP), characterized by diffuse J-point elevation and concave ST-segment elevation, and long regarded as a normal variant. However, recently published data suggest that the ERP may be a marker of increased risk for sudden cardiac death (SCD) in the general population. The observation that the ERP can indicate increased SCD risk has important implications for the clinician charged with the care of athletes. This review will describe the evolving understanding of the ERP and will explore the relevance of the ERP for the care of athletes